Autonomous vehicles: the legal landscape of using and testing autonomus cars in Poland - Jaworski, Bartłomiej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
Due to expected benefits of mass-use of the autonomous vehicles, specialists in many fields are trying hard to overcome all barriers related to the development and planned spreading of this way of transport. In fact, technology allows to use autonomous vehicles for years, but the real barriers to their mass-use are sociological and legal problems, which are much harder to overcome. The purpose of this paper is to analyze the amendment to the Polish Road Transport Act, which introduce the legal definition of an autonomous vehicle and defines the conditions for using and testing the autonomous vehicles on Polish public roads. This text is a brief characterization of current understanding of autonomous vehicles and it points out the sociological and legal barriers that exist on the way to their widespread use.
Keywords: technology; autonomous vehicle; legal barriers